Solvothermal synthesis of β-tricalcium phosphate porous nanospheres by using organic phosphorus source and their biomedical potentials1. Issue 30 (3rd April 2015) - Zhu, Genxing; Hu, Yadong; Yang, Yuling; Zhao, Ruibo; Tang, Ruikang
<x xml:space="preserve">Abstract</x> Uniform β-tricalcium phosphate porous nanospheres with substructures are prepared by a solvothermal method using (CH3O)3PO as the organic phosphorus source and they demonstrate excellent biocompatibility.